2011
DOI: 10.3174/ajnr.a2708
|View full text |Cite
|
Sign up to set email alerts
|

Brain Perfusion in Asphyxiated Newborns Treated with Therapeutic Hypothermia

Abstract: Background and Purpose Induced hypothermia is thought to work partly by mitigating reperfusion injury in asphyxiated term newborns. The purpose of this study is to assess brain perfusion in the first week of life in these newborns. Patients and Methods In this prospective cohort study, magnetic resonance imaging (MRI) and perfusion imaging by arterial spin labeling (ASL-PI) was used to assess brain perfusion in these newborns. We measured regional cerebral blood flow values on 1–2 MRIs obtained during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 43 publications
(64 reference statements)
12
108
3
1
Order By: Relevance
“…Although our sample size is small, our data are consistent with two other studies reporting an increased cerebral blood flow beyond 24 hours after the initial insult in TH-treated newborns with HIE who develop more severe brain injury (23,24). Two explanations may account for this cephalic redistribution of LVCO in TH-treated newborns with brain injury.…”
Section: Discussionsupporting
confidence: 81%
“…Although our sample size is small, our data are consistent with two other studies reporting an increased cerebral blood flow beyond 24 hours after the initial insult in TH-treated newborns with HIE who develop more severe brain injury (23,24). Two explanations may account for this cephalic redistribution of LVCO in TH-treated newborns with brain injury.…”
Section: Discussionsupporting
confidence: 81%
“…This observation was also consistent with a previous MRI study that showed decreased cerebral perfusion in acute neonatal HIE with hypothermia. 26 Although MRI methods for estimating CMRO 2 have been published in the adult literature, [27][28][29][30][31] there is currently little data on the MRI measurement of CMRO 2 in neonates. One recent abstract reported results for 6 normothermic preterm infants without acute brain injury.…”
Section: Indices Of Cerebral Oxygen Metabolism and Cerebral Blood Flowmentioning
confidence: 99%
“…First of all, most of these modalities require a contrast agent, which qualifies it as invasive: gadolinium derivatives in the case of MRI, iodine or barium compounds in the case of computed tomography angiography. Some modalities such as Arterial Spin Labeling, 27 Phase-contrast MR Angiography, or Cineangiography by MR global coherent-free precession 29 avoid the use of contrast agent but their resolution is limited (800 mm for the last one) compared with our 250 mm Ultrafast Doppler resolution. The rapidity of the acquisition process must be underlined: a decent quality Power Doppler Image is obtained with 400 ms of acquisition (one preterm infant cardiac cycle), and 1 second of acquisition gives a very good quality image (the quality of the Doppler images generally increases with the duration of the acquisition, but after 1.5 seconds of acquisition movement artifact can occur and blur the vascular paths).…”
Section: Discussionmentioning
confidence: 99%
“…On each ROI, the mean value of the resistivity and its standard deviation Effect of Therapeutic Hypothermia (for Hypoxo Ischemic Encephalopathy) and Rewarming on the Cerebral Resistivity As a clinical illustration of the capability of resistivity maps to give easily readable clinical information on the resistivity of the vascular network, serial examinations have been performed on a full-term infant subjected to therapeutic hypothermia after neonatal hypoxo ischemic encephalopathy. 27,28 The patient was maintained under mild whole-body hypothermia (33.51C) from 6 hours of life and for 72 hours. When the period of cooling concluded, rewarming was cautiously conducted and the servocontrolled rectal temperature was allowed to rise by no more than 0.51C per hour, to a maximum of 36.5±0.21C.…”
Section: Quantitative Data Mapping With Ultrafast Doppler Imagingmentioning
confidence: 99%